2005
DOI: 10.1002/ptr.1710
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes in Leydig cells and cauda epididymal spermatozoa induced byAzadirachta indica leaves in albino rats

Abstract: The effects of Azadirachta indica leaves (500 mg/kg body weight, orally/day), testosterone (0.25 mg/kg body weight/day, intramuscularly) and a combination of these two were investigated as to whether Azadirachta indica leaves affect the morphology of Leydig cells and epididymal sperm and their organelles at the ultrastructural level. Azadirachta indica treated rats showed atrophic seminiferous tubules with widening intercellular spaces. Leydig cells exhibited characteristics of degeneration such as indented nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Treatment with different parts of the plants such as leaf powder of Azadirachta indica [24,25] crude garlic [23] and benzene extract of O. sanctum leaves [22] on ultrastructure of the rat testis revealed several changes and it can be summaries in three categories such as: (i) vacuolization in the Sertoli cells and germ cells; (ii) degeneration of mitochondria followed by vacuolization in spermatocytes and spermatids; and (iii) a decrease in nuclear density and ruptures of plasmatic membranes. Studies from Aladakatti and Nazeer Ahamed [22,24] and Alladakatti et al [25] have shown that Azadirachta indica leaf powder and benzene extract of Ocimum sanctum leaves cause the disruption of intercellular bridges between germ cell-germ cells, germ cells-Sertoli cells or Sertoli cells-Sertoli cells in rats due to their antiandrogenic properties. In view of the dynamic role of androgen in the initiation and maintenance of spermatids, it is believed that the degenerative changes observed in the spermatids may be due to deprivation of androgens.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with different parts of the plants such as leaf powder of Azadirachta indica [24,25] crude garlic [23] and benzene extract of O. sanctum leaves [22] on ultrastructure of the rat testis revealed several changes and it can be summaries in three categories such as: (i) vacuolization in the Sertoli cells and germ cells; (ii) degeneration of mitochondria followed by vacuolization in spermatocytes and spermatids; and (iii) a decrease in nuclear density and ruptures of plasmatic membranes. Studies from Aladakatti and Nazeer Ahamed [22,24] and Alladakatti et al [25] have shown that Azadirachta indica leaf powder and benzene extract of Ocimum sanctum leaves cause the disruption of intercellular bridges between germ cell-germ cells, germ cells-Sertoli cells or Sertoli cells-Sertoli cells in rats due to their antiandrogenic properties. In view of the dynamic role of androgen in the initiation and maintenance of spermatids, it is believed that the degenerative changes observed in the spermatids may be due to deprivation of androgens.…”
Section: Discussionmentioning
confidence: 99%
“…The leaves of Azadirachta indica when administered orally at a dose of 500 mg per kg body weight exhibited a regression and decrease in the number of Leydig cells and their nuclear diameter, indicating androgen deficiency[46]. The aqueous extracts leptadenia hastata when administered orally at varying doses per kg body weight exhibited anti-androgenic property[47].…”
Section: Steroidogenesis and Medicinal Plantsmentioning
confidence: 99%
“…A linear decrease in the percentage of sperm motility was observed with various concentrations (1–50 mg per 1 million sperm) of neem leaf extract, with motility falling to absolute zero within 20 seconds of exposure to 3 mg dose[68]. Atrophy of the Leydig cells was observed when the leaf extracts of Azadirachta indica and flower extract of Malvaviscus conzattii were administered to male albino rats[466970]. The aqueous leaf extract of neem when administered to male mice at a dose of 200 mg kg –1 for 28 days damaged the seminiferous tubules, resulting in the slackening of germinal epithelium, marginal condensation of chromatin in round spermatids, degeneration of germ cells and the derangement of germ cell types from their orderly arrangement in spermatogenesis[71].…”
Section: Spermatogenesis and Medicinal Plantsmentioning
confidence: 99%
“…Both the Thunder of God vine and the Neem Tree are used in traditional medicine practices to treat a variety of inflammatory and auto-immune diseases including cancer, and both natural products manifest anti-spermatogenic properties [141, 142]. This anti-spermatogenic capacity is shared with another Hsp90 inhibitor, gamendazole, a synthetic small molecule [28].…”
Section: Strategies Of Hsp90 Inhibition and An Evaluation Of New Modumentioning
confidence: 99%